Perancangan Sistem Informasi Persediaan Obat Berbasis Web Pada Apotek Dermapink Tembesi - Husnul Fatiyah; Okka Raisa Lestari; Gilang Romadhan (Journal of Applied Accounting and Business, 2020)
Dermapink Pharmacy is a business entity engaged in the supply and sale of drugs. The process of recording data in and out of drugs contains a lot of duplicate data and a high error rate to process data and produce the necessary reports. With that in order to be optimal, it is advisable to use an inventory information system. The purpose of this study was to design a drug supply information system at Dermapink Tembesi pharmacies in accordance with correct accounting standards. Methods of data collection are done by means of interviews, observation, documentation and analysis of the systems used by the company. The result of this research is to produce a web-based inventory information system with the FIFO method which provides convenience in providing information on inventory data through incoming and outgoing goods using data flow diagrams, DFD, ERD and MySQL for data processing. The result of this research is that the existence of this inventory system can produce reports of incoming and outgoing drug stock expenditures per period more quickly, efficiently and accurately and facilitate the processing of drug purchase and sale transaction data at the Dermapink Pharmacy.